Modeling of aqueous suspension filtration when combining downward and upward flows - Poliakov, V.L.; Kurganska, S.M. (Доповіді НАН України, 2025)
The physical domain is divided into two subareas of motion, and a nonlinear mathematical problem of water suspension filtration with linear kinetics of interphase detachment mass transfer is formulated with respect to each of them. The structure of gel-like deposit, the dependence of hydraulic conductivity on its concentration, and the relationship of mass transfer coefficients (attachment and detachment) with the filtration rate are taken into account. The corresponding mathematical models contain interconnected clarification and filtration flow compartments. After the introduction of dimensionless variables and parameters, as well as the application of the operational method, rigorous solutions of both problems are obtained. As a result, the most important dependencies and equations were derived for engineering calculations of key characteristics of filtration — concentration of dispersed impurity in filtrate and head losses in distinguished subareas and common in the whole operating layer. The mentioned formalisms were used to determine the main technological times, which limited the time of continuous filter operation due to excessive deterioration of the filtrate quality and mechanical energy consumption for filtration through the clogged medium. As a consequence, the permissible time of its continuous operation (filter run) based on the criteria of effective filtration was established. The similar technological approach to the estimation of the filter performance was applied in parallel to the high-rate filter at the traditional single-fl ow suspension feeding and the two-fl ow feeding investigated above. Comparative analysis was performed on test examples with typical initial data for practice of clarification of aqueous suspensions. As a result, it was obtained that the division of the initial flow of suspension into two components coming through the upper and lower bed surfaces can contribute to a significant intensification of the technological process. At the same time, it is realistic to increase the duration of filter runs by 50 % and more, which leads to a tangible decrease in the cost of filtrate. Thus, application of well sorbing filtering materials becomes justified. Фізичну область розділено на дві підобласті руху, і стосовно кожної з них сформульовано нелінійну математичну задачу фільтрування водної суспензії за лінійної кінетики міжфазного відривного масообміну. При цьому враховано структуру гелеподібного осаду, залежність від його концентрації коефіцієнта фільтрації, зв’язок коефіцієнтів масообміну (прилипання та відриву) зі швидкістю фільтрування. Відповідні математичні моделі містять взаємопов’язані освітлювальний і фільтраційний блоки. Після введення безрозмірних змінних і параметрів, а також застосування операційного методу отримано суворі розв’язки обох задач. У підсумку виведено найважливіші залежності та рівняння, призначені для інженерних розрахунків ключових характеристик фільтрування — концентрації дисперсної домішки у фільтраті та втрат напору у виділених підобластях і загальних у всьому шарі завантаження. Зазначені формалізми використовували для визначення основних технологічних часів, що обмежувало час безперервної роботи фільтра внаслідок надмірного погіршення якості фільтрату та витрат механічної енергії на фільтрацію через засмічене середовище. Як наслідок, встановлювали допустимий виходячи з критеріїв ефективного фільтрування час його безперервної роботи. Подібний технологічний підхід до оцінки працездатності фільтра паралельно застосовували до швидкого фільтра за традиційної однопотокової подачі суспензії та дослідженої вище двопотокової. Порівняльний аналіз виконано на тестових прикладах з типовими для практики освітлення водних суспензій вихідними даними. У результаті отримано, що поділ вихідного потоку суспензії на дві складові, що надходять через верхню та нижню поверхні завантаження, може сприяти значній інтенсифікації технологічного процесу. При цьому реально збільшення тривалості фільтроциклів на 50 % і більше, що призводить до відчутного зниження вартості фільтрату. Таким чином, стає виправданим застосування фільтрувальних матеріалів, що добре сорбують.